Pemetaan, Karakterisasi, dan Pengembangan Primer-primer Lokus Pup1 (P uptake 1) pada Padi untuk Peningkatan Toleransi terhadap Defisiensi Fosfor - Joko Prasetiyono; Tasliah Tasliah (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Phosphorus (P) is the second most important nutrient forplants after nitrogen, but is available in very low amount. Pdeficiency in rice would reduce the number of tillers andgrain production. There are numerous publications onexploration of genes that are associated with P. Manyresearches on P that are directed to breeding program andinvolving many countries/institutions focus on Pup1research. Pup1 (P uptake 1) is associated with P uptake hasbeen well mapped on chromosome 12 at a distance of 15.31to 15.47 Mb and microsatellite markers between RM28073and RM28102 can be used as a selection tool in the MAB(Marker Assisted Backrossing) program. Indonesia is veryconcerned with this research because of P-deficientproblem. This review aims to provide current information ofresearch that explore the genes in Pup1 locus. This reviewoutlines the history of Pup1 mapping, to explain sequenceand expression analysis of Pup1, and to inform of Pup1specific primers. The latest information is expected to beuseful for rice breeders in Indonesia, especially for thosewho are interested to P deficiency research. Study of geneswithin Pup1 locus is still ongoing, and found that somegenes do not contribute directly to P uptake. This mayindicate that Pup1 locus use other mechanisms in the Puptake. This may indicate that some genes (dirigent-like,fatty acid α-dioxygenase, aspartic proteinases) play a role inthe increasing level of lignin in P deficient condition.Increasing level of lignin would increase the volume of rootsand thus increasing P uptake and resistance to biotic andabiotic stresses. Specific markers to detect the genes in thePup1 locus have been successfully developed, and can beused for breeding and exploration activities on Indonesianrice germplasm.